Citation Data and Analysis: Limitations and Shortcomings - Worrall, John L. (Journal of contemporary criminal justice, 2023)
As a means for measuring scholarly influence, citation analysis has several limitations and shortcomings. We first review the main sources of citation data (Web of Science, Scopus, Google Scholar, and information collected directly from reference lists) and discuss the shortcomings of each source. Next, we review five significant limitations of citation analysis as a methodology (academic over popular interest, various motivations for citing, manipulation potential, failure to account for author ordering, and citations only appearing in “indexed” journals). The issues we touch on set the stage for the remainder of the articles in this special issue.